W poszukiwaniu genezy i specyfi ki zjawiska ekstazy w religiach Bengalu = SEARCHING FOR THE ORIGIN AND NATURE OF THE PHENOMENON OF ECSTASY IN THE RELIGIONS OF BENGAL - Czyżykowski, Robert (2011)
In the religions of Bengal ecstasy is the culmination and test of religious maturity and the state of adulthood, the external expression of unio mystica and the effect of possession by a deity. Ecstasy confirms and provides meaning to religious practices, and the exceptional bodily states that accompany it provide religion with the marks of authenticity -one might say that ecstasy is the actualisation of the myth and model of the perfect person that can be found in Bengali culture. The ecstatic usually fulfils the function of guru -the verification of the authenticity of his bhava (ecstatic state) works as a legitimisation of his status as a religious teacher. Ecstasy can be induced by ritual means, asceticism and discipline -such ecstasy can be called ritual. In the other case it has the nature of spontaneous experience, and in this case it is perceived as a sign of the particular blessing of the deity. This understanding of the phenomenon of ecstasy is convergent with the concept of religion as a mystical state providing meaning as well as offering a person exceptional visionary experiences that are not present in ordinary life. In this way ecstasy would be the realisation of the innate human potential to enter altered states of consciousness (ASC), which constitute an integral component of traditional cultures. Such states are experienced by the participants of a given community in accordance with the model operating in that culture, and are the legitimisation of the knowledge passed on according to tradition. On the other hand, these states continually verify that model, and sometimes go beyond it, introducing new elements into the culture and specific religious tradition.
Keywords: Bengal; Tantra; Vaishnavism; Ecstasy; Mysticism